Distortion of the Coordination Structure and High Symmetry of the Crystal Structure in In4SnS8 Microflowers for Enhancing Visible-Light Photocatalytic CO2 Reduction - Chai, Yao; Chen, Yanmei; Shen, Jinni; Ni, Mengmeng; Wang, Bing; Li, Dongmiao; Zhang, Zizhong; Wang, Xuxu (ACS catalysis, 2021)
Modulating the crystal structure of the semiconductor photocatalyst is important to separate and migrate the photogenerated electrons and holes for good photocatalytic performance. Here, we show that Sn replaces part of In atoms in In2S3 nanosheets to form bimetallic sulfide In4SnS8, which induces the distortion of the [InS6] octahedron and improves the crystal symmetry of the spatial arrangement of [SnS6] and [InS6] octahedrons. The twisted [InS6] octahedron can promote the separation of photogenerated carriers. The improved symmetry of the crystal structure promotes the migration of separated electrons through reducing the lattice scattering effect of the crystal structure, which is favorable to the rapid transfer of electrons from the bulk to the surface. Both endow In4SnS8 with generation rates of CH4 and CO about 20 and 12 times higher than those of In2S3 and SnS2 for the catalytic CO2 photoreduction reaction, respectively. This work offers basic guidance to rationally design a photocatalyst for the improved separation of photoinduced electron/hole pairs.